Street Vendors and Halal-Thayyib Business Practices: An Ethnographic Study in the Context of Religious Moderation - Amaroh, Siti; Husnurrosyidah, Husnurrosyidah (Prodi Ekonomi Syariah Pascasarjana IAIN Kudus, 2024)
This study explores the understanding of street vendors in Kudus Regency regarding the halal-thayyib paradigm and the challenges they face in its implementation. The research was conducted with 11 informants from various areas: City Walk, Alun-Alun Simpang 7, Pasar Kliwon, Museum Kretek, and Bale Jagong. The data analysis technique used ethnographic analysis to describe the societal situation based on the meanings and values embraced. Observations reveal that street vendors encounter various obstacles, including limited sanitation facilities, the use of supplementary materials with uncertain halal status, and a lack of in-depth understanding of the halal concept. Most street vendors prioritize economic profit over adherence to halal principles. Nevertheless, street vendors have demonstrated increased awareness of halal through socialization and education programs. While halal certification appears to be an appealing prospect, they perceive the costs as high and the procedures as complex. The aspect of religious moderation is reflected in the tolerance among individuals of different faiths, where non-Muslim are aware of halal requirements but still require further education. This study suggests empowering street vendors through religious moderation as a solution to enhance their understanding of halal, while also meeting market demands and improving their economic welfare.